Pengaruh audit internal dan digitalisasi terhadap pencegahan kecurangan dalam laporan keuangan pada perusahaan manufaktur - Zulfa, Anis Azkiyah (Maliki Interdisciplinary Journal, 2025)
Internal audit and digitalization have increasingly become crucial elements in addressing the risk of financial fraud, particularly in manufacturing companies that are characterized by high operational complexity. The main challenge faced by these companies lies in the vulnerability of financial data to manipulation and the limitations of manual monitoring systems in ensuring accuracy and accountability. This study aims to analyze the influence of internal audit and digitalization on the prevention of financial fraud in the financial statements of manufacturing companies in Indonesia. The research employed a quantitative approach using survey methods, in which questionnaires were distributed to a number of manufacturing firms. The collected data were then analyzed through regression techniques to examine the relationship between internal audit, digitalization, and fraud prevention. The findings reveal that a well-structured and effective internal audit significantly reduces the likelihood of fraudulent practices, particularly when reinforced by the adoption of digitalized financial systems. Digitalization contributes by enhancing transparency, minimizing human errors, and strengthening transaction traceability, thereby narrowing opportunities for manipulation in financial reporting.